(untitled) (Scientific journal of the Fergana State University, 2023)
This article discusses methods for analyzing concepts in cultural linguistics, and it is recommended to first select a representative of the concept. By classifying dictionary definitions, the conceptual component is determined and the symbolic, ironic, and metaphorical meanings associated with them are considered. Characterizing stereotypes characteristic of a particular linguistic culture allows us to become more familiar with the conceptual and figurative characteristics of the concepts involved in the analysis. By analyzing concepts, one can generalize their features in a particular linguistic culture and draw conclusions about the changes occurring in them over time.